2013
DOI: 10.3233/jad-130209
|View full text |Cite
|
Sign up to set email alerts
|

Increased Iron Levels and Decreased Tissue Integrity in Hippocampus of Alzheimer's Disease Detected in vivo with Magnetic Resonance Imaging

Abstract: The data shows that in AD, Hipp damage occurs in conjunction with ferritin iron accumulation. Prospective studies are needed to evaluate how increasing iron levels may influence the trajectory of tissue damage and cognitive and pathologic manifestations of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
146
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(157 citation statements)
references
References 99 publications
7
146
2
2
Order By: Relevance
“…MRI transverse relaxation rates R2 [42][43][44][45] and R2* 43,[46][47][48] correlate with brain iron concentration, although they are affected by tissue fluid content. Field dependent relaxation rate increase imaging (FDRI) 42,49,50 and quantitative susceptibility mapping (QSM) [51][52][53][54][55] are more recent advances in brain iron imaging. FDRI utilizes imaging at two different field strengths, allowing the calculation of a parameter independent of tissue liquid content, which correlates with reported values of brain iron.…”
Section: Other Mri Techniques Of Interestmentioning
confidence: 98%
“…MRI transverse relaxation rates R2 [42][43][44][45] and R2* 43,[46][47][48] correlate with brain iron concentration, although they are affected by tissue fluid content. Field dependent relaxation rate increase imaging (FDRI) 42,49,50 and quantitative susceptibility mapping (QSM) [51][52][53][54][55] are more recent advances in brain iron imaging. FDRI utilizes imaging at two different field strengths, allowing the calculation of a parameter independent of tissue liquid content, which correlates with reported values of brain iron.…”
Section: Other Mri Techniques Of Interestmentioning
confidence: 98%
“…74 Alzheimer disease (AD) has also been associated with disrupted iron metabolism in the brain, and iron accumulates in the rims of amyloid-β (Aβ) plaques 75 and in neurofibrillary tangles. 76 Despite some suggestion of citation bias with respect to iron accumulation in AD, 77 several studies [78][79][80][81] have confirmed that iron levels are elevated in various brain regions in this disease. Cortical accumulation of iron has also been identified in acute relapses of multiple scler osis; paradoxically, however, iron levels decrease in chronic cases.…”
Section: Iron In the Ageing Brainmentioning
confidence: 99%
“…Alzheimer's disease involves multifactorial brain changes including problems with amyloid and tau processing, neuronal degeneration, insulin dysregulation, synaptic loss, chronic inflammation, oxidative stress, and accumulation of metals [1][2][3]. The disruption of metal homeostasis has led to the suggested use of metal-binding agents as a potential therapeutic strategy [3].…”
Section: Introductionmentioning
confidence: 99%
“…The disruption of metal homeostasis has led to the suggested use of metal-binding agents as a potential therapeutic strategy [3]. Metalbinding agents currently being developed for the treatment of AD include clioquinol, PBT2, M30, and deferoxamine [4].…”
Section: Introductionmentioning
confidence: 99%